In silico comparative analysis of crispr-cas system structures of Yersinia pseudotuberculosis causing different clinical manifestations of pseudotuberculosis - N. P. Peretolchina; Yu. P. Dzhioev; A. Yu. Borisenko; L. A. Stepanenko; E. A. Voskresenskaya; V. T. Klimov; O. N. Reva; V. I. Zlobin (Журнал инфектологии)
The aim of this research was to analyze and compare CRIPSR loci and cas-proteins of Yersinia pseudotuberculosis strains isolated in different territories from patients with various clinical manifestations of pseudotuberculosis.Materials and Methods. Complete genomes of Y. pseudotuberculosis IP329353 (NC_006155) and IP31758 (NC_009708) were obtained from NCBI Nucleotide Database. Strains were isolated from patients with gastroenteritis and systemic infection respectively. Search, identification, and analysis of CRISPR systems were carried out by onlinetools CRISPROne, CRISPRDetect, and CRISPRTarget.Results. Analyzed strains have CRISPR-Cas systems that include one set of cas-genes and arrays situated at the long distances from each other. We defined three CRISPR arrays in Y. pseudotuberculosis IP32953: array YP1 located near cas-genes, arrays YP2 and YP3. CRISPR-Cas system of Y. pseudotuberculosis IP31758 includes two arrays – YP1 and YP3. CRISPR systems do not share similar spacers.Conclusion. CRISPR systems of the analyzed strains differ in CRISPR loci and cas-protein structures that can be used as specific molecular marks of analyzed strains during the study of intra-species variability and evolution of Y. pseudotuberculosis.